Playing-related musculoskeletal problems in children learning instrumental music: prevalence and associated potential risk factors - Ranelli, Sonia (Curtin University, 2012)
731 child instrumentalists were surveyed to establish the 1) prevalence and location of PRMP, and 2) independent association of potential risk factors with PRMP. 67% reported lifetime prevalence of PRMP, 56% monthly PRMP and 30% were unable to play the instrument as usual. The hands and neck were the most commonly reported PRMP locations. Individual factors and music-related factors were significantly associated with PRMP. Understanding potential risk factors will guide intervention initiatives for young instrumentalists.